THE INTERPLAY OF INVESTOR PSYCHOLOGY, ACCOUNTING INFORMATION, AND FINTECH IN SHAPING INVESTMENT DECISIONS: EVIDENCE FROM OMAN - Zaheeruddin , Mohamed; Kumar , Suneel (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The rapid economic revolution in Oman over the recent years has flickered an increased awareness of behavioral finance, investment tactics, and financial know-how. Traditional finance theories often overlook the role of biases and heuristics in investment decisions, particularly in developing markets like Oman, where financial literacy and technological adoption are still evolving. The primary goal of this study is to investigate the impact of investors’ psychology, accounting information, and fintech exposure on investment decisions among individuals in Oman. The study focuses on evaluating how these factors impact the investment interest and decision-making processes among Omani individuals, particularly examining the mediating role of investment interest in these relationships. A quantitative research approach was adopted, utilizing a structured questionnaire distributed among Omani individuals. Data was collected from 504 respondents to analyze their investment psychology, access to accounting information, and level of fintech adoption. The survey-based methodology enabled a comprehensive examination of the relationships between these factors and investment decision-making. The study found that investor psychology enhances investment interest, which further influences investment decisions positively. The results of this study show a positive impact of available information on investment interest and investment decisions. Additionally, exposure to fintech platforms enables more informed decision-making. The findings of this study suggest that investor psychology, accounting information, and fintech exposure significantly shape investment decisions by enhancing investment interest and facilitating better decision-making among individuals in Oman. JEL Classification Codes: G41.